Enhancing Student’s Interest in Learning and Science Problem-Solving Skills through Educational Comics - Utami, Candra Tri; Kawuryan, Sekar Purbarini; Astuti, Pratiwi Puji; Sugara, Ujang (Universitas Pendidikan Ganesha, 2024)
Students still have difficulties in developing their interest in learning and the ability to solve science problems. This has an impact on students having difficulty working in groups, communicating, solving problems, and making decisions as the right solution to a problem. The objectives of this study are (1) to analyze whether there is a difference in learning interest and science problem-solving ability of students who use educational comics and students who do not use educational comics (2) to analyze the influence of educational comics on the increase in learning interest and science problem-solving ability in students. This research is expected to provide data about the use of comics in improving students' problem-solving abilities and interest in learning. This research was carried out with the research subject in the form of 5th grade elementary school students. This study uses a quasi-experimental design with a pretest-posttest control design. The data collection method uses research instruments in the form of questionnaires and tests. The data analysis technique used is quantitative descriptive analysis. Based on the hypothesis test, the independent t-test with a significant level (a) of 0.05 obtained a significance value of 0.000 and the paired sample t-test with a significance level of (a) 0.05 obtained a significance value of 0.000. Thus, it can be concluded that there is a difference in learning interest and science problem-solving ability between students who use educational comics and students who do not use educational comics, educational comics also affect the increase in learning interest and science problem-solving skills of 5th grade elementary school students.